2021
DOI: 10.1101/2021.03.24.436884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of STAT5 in adipocytes increases subcutaneous fat mass via sex-dependent and depot-specific pathways

Abstract: The STAT (Signal Transducers and Activators of Transcription) family of transcription factors contributes to adipocyte development and function. STAT5A and STAT5B are induced during adipocyte differentiation and are primarily activated by growth hormone (GH). Studies in mice lacking adipocyte GH receptor or STAT5 support their roles in lipolysis-mediated reduction of adipose tissue mass. We have generated a mouse model lacking both STAT5 genes specifically in adipocytes (STAT5AKO). Notably, both sexes of STAT5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Remarkably, the impaired lipolysis observed in lean Stat5 Adipoq mice was associated with improved whole-body insulin sensitivity [ 11 ]. While these attributes may in part be sex-specific [ 14 ], similar effects have been reported in mouse models with adipocyte-specific deletion of adipose triglyceride lipase (ATGL) [ 15 ] as well as of other mediators of GH-signalling (i.e., GH receptor [ 16 ], JAK2 tyrosine kinase [ 17 ]).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Remarkably, the impaired lipolysis observed in lean Stat5 Adipoq mice was associated with improved whole-body insulin sensitivity [ 11 ]. While these attributes may in part be sex-specific [ 14 ], similar effects have been reported in mouse models with adipocyte-specific deletion of adipose triglyceride lipase (ATGL) [ 15 ] as well as of other mediators of GH-signalling (i.e., GH receptor [ 16 ], JAK2 tyrosine kinase [ 17 ]).…”
Section: Introductionmentioning
confidence: 94%
“…The signal transducer and activator of transcription (STAT5) plays a central role in adipose tissue with involvement in the regulation of adipogenesis [ 6 ], adipocyte differentiation [ 7 ], fat browning [ 8 , 9 ], adaptations to food restriction [ 10 ], brown adipose tissue thermogenesis [ 10 ], and lipolysis [ 11 ]. Specifically, there is evidence that STAT5A and STAT5B mediate the mobilisation of lipid from the adipocyte induced by growth hormone (GH) [ 12 , 13 ], albeit recent findings suggest that GH may modulate lipolysis also in a STAT5-independent manner [ 14 ]. We recently reported that male mice lacking both STAT5 proteins in their mature adipocytes ( Stat5 Adipoq mice) show impaired lipolysis in white adipose tissue and increased accumulation of subcutaneous fat mass [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these challenges, many researchers interested in studying metabolic function using mouse models have transitioned to housing within the thermal neutral zone (28-30 • C). A few groups focusing on the GH-axis function have implemented this strategy [48][49][50], but none, to date, have specifically studied the impact on the GH-mediated regulation of hepatic metabolism under thermoneutral conditions.…”
Section: Metabolic Actions Of Gh/ghr Can Be Mediated By Multiple Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…However, this GH-mediated impairment in canonical insulin signaling has not been observed in humans. The anti-insulin effects of GH in adipocytes may be mediated by STAT5, since the adipocyte-specific loss of either GHR [103] or STAT5 [50,104] leads to an increase in adipose tissue mass under chow-fed conditions and improves whole body insulin sensitivity. However, in contrast to the adipocyte-specific loss of GHR, the loss of adipocyte STAT5 is not associated with a reduction in WAT lipolysis and does not impact the ability of GH treatment to reduce WAT mass [50].…”
Section: Gh Antagonizes the Actions Of Insulin In A Tissue-and Context-specific Mannermentioning
confidence: 99%